Analyzing the New York Global History and Geography Exam - Grant, S. G. (Education Policy Analysis Archives, 2001)
Education Week's report "Quality Counts" judges New York State's curriculum and assessment policy efforts to be an "A." Surface-level reviews such as "Quality Counts" tell something about the workings of state policy, but they are more useful as snapshots than as well-developed portraits of curriculum and assessment change. In this article, I analyze the new New York State Global History and Geography standards and tests using a set of social studies-specific criteria which inquire deeply into the implications for real instructional change. From that vantage, I argue that New York's policy efforts, while seemingly well-intentioned and reflective of surface-level change, fail to promote powerful teaching and learning in social studies. Teachers intent on producing ambitious teaching and learning will find little to interfere with their efforts. But as a set of reforms intended to encourage substantive change, the new global history test falls short.